Using the Plasmodium mitochondrial genome for classifying mixed-species infections and inferring the geographical origin of P. falciparum parasites imported to the U.S. - Schmedes, Sarah E. (PLoS One, 2019)
The ability to identify mixed-species infections and track the origin of Plasmodium parasites can further enhance the development of treatment and prevention recommendations as well as outbreak investigations. Here, we explore the utility of using the full Plasmodium mitochondrial genome to classify Plasmodium species, detect mixed infections, and infer the geographical origin of imported P. falciparum parasites to the United States (U.S.). Using the recently developed standardized, high-throughput Malaria Resistance Surveillance (MaRS) protocol, the full Plasmodium mitochondrial genomes of 265 malaria cases imported to the U.S. from 2014–2017 were sequenced and analyzed. P. falciparum infections were found in 94.7% (251/265) of samples. Five percent (14/265) of samples were identified as mixed- Plasmodium species or non-P. falciparum, including P. vivax, P. malariae, P. ovale curtisi, and P. ovale wallikeri. P. falciparum mitochondrial haplotypes analysis revealed greater than eighteen percent of samples to have at least two P. falciparum mitochondrial genome haplotypes, indicating either heteroplasmy or multi-clonal infections. Maximum-likelihood phylogenies of 912 P. falciparum mitochondrial genomes with known country origin were used to infer the geographical origin of thirteen samples from persons with unknown travel histories as: Africa (country unspecified) (n = 10), Ghana (n = 1), Southeast Asia (n = 1), and the Philippines (n = 1). We demonstrate the utility and current limitations of using the Plasmodium mitochondrial genome to classify samples with mixed-infections and infer the geographical origin of imported P. falciparum malaria cases to the U.S. with unknown travel history.